Assessment of the risks of impacts of heavy metals and arsenic entering the human body with herbal medicines - M. S. Galenko; I. V. Gravel (Разработка и регистрация лекарственных средств)
Introduction. Liquid dosage forms based on medicinal plant raw materials are very convenient to use and must meet safety requirements. In the context of harmonization of pharmacopoeial requirements, determining the total content of heavy metals in tinctures is not enough. Risk assessment is necessary to calculate the permissible concentrations of heavy metals in tinctures.Aim. To assess the safety of using tinctures in terms of the content of heavy metals and arsenic within the framework of a risk-oriented strategy.Materials and methods. The objects of the study were 20 samples of valerian and motherwort tinctures manufactured by various enterprises. The quantitative content of 15 elements (As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Mo, Ni, Pb, Sr, Tl, V, Zn) was determined by inductively coupled plasma mass spectrometry.Results and discussion. The concentrations of elements in tinctures varied in the range of 0–1.84 μg/g. Manganese and zinc were found in maximum quantities, while cadmium, molybdenum and vanadium were found in minimum quantities. Mercury was not detected in any of the samples. The content of toxic elements in the tinctures did not exceed the levels of permissible concentrations regulated by the normative documentation of the Russian Federation. Total hazard indices (HI) were calculated at the levels of the median and 90th percentile of the content of elemental toxicants. In the tinctures, they were, respectively: valerian – 0.016 · 10–5 and 0.027 · 10–5, motherwort – 0.022 · 10–5 and 0.028 · 10–5. The obtained values were significantly lower than 1.0. Calculation of individual carcinogenic risk (CR) of elemental carcinogens (Cd, As, Cr, Pb) entering the body with tinctures of valerian and motherwort showed that the CR values were in the range of 4.9 · 10–9–6.84 · 10–7, which did not exceed the permissible threshold value (1 · 10–6).Conclusions. The actual content of toxic elements (Pb, Cd, As, Hg) in tinctures of valerian and motherwort was 0–0.006 μg/g, which did not exceed the levels of permissible concentrations. Calculations of non-carcinogenic risks when using tinctures of valerian and motherwort showed that the total impact of 15 studied elements on human health when consuming a daily dose of tinctures is characterized as permissible, periodic monitoring of the content of non-standardized elements in samples of herbal medicines is not required. It was established that the studied tinctures of valerian and motherwort are not oncogenic factors and do not require risk reduction measures.